Determinants of Demand and Supply of Accounting and Audit Services in SMEs: Evidence from Nigeria - Semiu Babatunde Adeyemi; Sunday Obah; Ini Etete Udofia (Journal of Accounting and Management Information Systems (JAMIS), 2015)
The study investigated the factors that determine the demand and supply of accounting and audit services in small and medium enterprises (SMEs), with evidence from Lagos, Nigeria. It also sought to know whether accounting and audit services contribute to the success of SMEs. The study made use of survey design. Using a structured questionnaire, evidence was collected from 380 respondents comprising of 300 SME owner-managers and 80 accounting firms. The data collected were analysed using both the descriptive and inferential statistics. The research findings indicated that owner-managers' characteristics, legal structure, education of managers, possession of accounting skills by managers and capital structure influence demand, while legal structure, attitude towards marketing, Government policy and owner-managers' characteristics influence supply of accounting and audit services. Findings also indicated that services of accountants and auditors have significant influence on the success of SMEs. The study recommended that owner-managers of SMEs should be given proper orientation on the importance of accounting and audit services to the success of their business. It was also recommended that Government should make the preparation and filing of audited accounts of SMEs mandatory, especially in order to render financial assistance to SMEs with a view to enhancing their socio-economic relevance. Accountants were also advised to take their services to the SMEs rather than waiting for the SME owner-managers to voluntarily call for their services.
Keywords: M41; M42; 650; SMEs; accounting and auditing services; theory of inspired confidence; agency theory; Nigeria